2009
DOI: 10.1182/blood-2009-01-200014
|View full text |Cite
|
Sign up to set email alerts
|

The thymus-independent immunity conferred by a pneumococcal polysaccharide is mediated by long-lived plasma cells

Abstract: It was recently shown that bacterial thymus-independent (TI) antigens confer long-lasting immunity and generate memory B lymphocytes. However, reactivation of TI memory B cells is repressed in immunocompetent mice, thus raising the issue of the mechanism whereby TI vaccines confer immune protection. Here, we propose an explanation to this apparent paradox by showing that a Streptococcus pneumoniae capsular polysaccharide (PS) generates long-lived bone marrow (BM) plasma cells which frequency can be increased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 36 publications
3
89
0
2
Order By: Relevance
“…1 proportionally to the maximum life span of humans, which is 122 y (69). An excellent example of the temporal appearance of shortlived plasmablasts in secondary lymphoid tissue and long-lived plasma cells in the bone marrow can be found in a study by Taillardet et al (68). Although this study uses mice, we have calculated that one mouse month is equivalent to ∼2.6 human years [based on a 4-y maximum life span (70)]; thus, the relative appearances of the three phases of circulating antibody and concomitant emergence of plasmablasts and plasma cells are in reasonable agreement between the two species.…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 98%
“…1 proportionally to the maximum life span of humans, which is 122 y (69). An excellent example of the temporal appearance of shortlived plasmablasts in secondary lymphoid tissue and long-lived plasma cells in the bone marrow can be found in a study by Taillardet et al (68). Although this study uses mice, we have calculated that one mouse month is equivalent to ∼2.6 human years [based on a 4-y maximum life span (70)]; thus, the relative appearances of the three phases of circulating antibody and concomitant emergence of plasmablasts and plasma cells are in reasonable agreement between the two species.…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 98%
“…However, various studies have shown that PPS induce efficient activation of IgM + memory B cells (IgM + IgD + CD27 + ) and generation of long-lived plasma cells (CD38 + CD20 low ). This is accompanied by the generation and persistence of IgM and IgG antibodies against PPS [101][102][103][104][105][106][107][108]. IgM + memory B cells circulating in the blood are the peripheral correlates of the marginal zone B cells of the spleen.…”
Section: Immunogenicitymentioning
confidence: 99%
“…However, ASC spot size was investigated following vaccination of a novel measles vaccine in mice, 30 and ASC spot size was found to vary following Streptococcus pneumoniae polysaccharide vaccination in mice with the presence or absence of a protein conjugate. 31 In the latter study, Taillardet et al demonstrated that the thymus-dependent, tetanus toxoid-polysaccharide conjugate formulation generated BM plasma cells with greater antibody secretion compared to a thymus-independent polysaccharide vaccine given with CpG adjuvant. 31 That study concluded that plasma cells activated by the different types of vaccines were functionally different.…”
Section: Discussionmentioning
confidence: 99%
“…31 In the latter study, Taillardet et al demonstrated that the thymus-dependent, tetanus toxoid-polysaccharide conjugate formulation generated BM plasma cells with greater antibody secretion compared to a thymus-independent polysaccharide vaccine given with CpG adjuvant. 31 That study concluded that plasma cells activated by the different types of vaccines were functionally different. Finally, although not strictly comparable to our mouse study, it is nonetheless interesting that Kim et al have recently reported that a high-dose of influenza antigen induces a striking effect on the pattern of immune responses in elderly subjects.…”
Section: Discussionmentioning
confidence: 99%